Upaya Pencegahan Anemia Ibu Hamil Melalui Pendidikan Kesehatan Menggunakan Media Monopoli Pintar pada Pelatihan Kader Kesehatan - Ramie, Agustine; Evy Marlinda; Rijanti Abdurrachim; Siti Afifah; Noor Maulidah; Noor Latifah Azlina (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
In 2025, cadre groups in the working area of Puskesmas Martapura Timur have mostly never been involved in education about health issues including the problem of anemia in pregnant women. This community service expects cadre groups to increase knowledge and skills about Anemia Prevention during pregnancy. The method used is to identify health problems, train health cadres to provide health education about anemia in pregnant women, healthy and nutritionally balanced foods to prevent anemia, self-care during pregnancy, and recognition of signs of anemia in pregnant women with a peer educator approach suitable for the field of health promotion to change knowledge, attitudes, and healthy living behavior. The results of community service showed an increase in knowledge and skills to 90%.